HSCT with mismatched unrelated donors: Bone marrow versus peripheral blood stem cells sources in pediatric patients. (28th January 2022) - Berger, Massimo; Barone, Marta; Spadea, Manuela; Saglio, Francesco; Pessolano, Rosanna; Fagioli, Franca
Abstract: Background: Allogeneic hematopoietic stem cell transplantation (HSCT) from an unrelated HLA‐mismatched donor (MMUD) is one of the alternatives where an HLA‐matched donor is not found. The aim of this study was to compare bone marrow (BM) versus peripheral blood stem cells (PBSC) as hematopoietic rescue following allogeneic unrelated mismatched stem cell transplantation (MMUD). Methods: The patients were divided into two groups: 43 pediatric patients were treated with BM and 17 pediatric patients with PBSC. The study was registered at ClinicalTrials.gov NCT04598789. Results: The 3‐year Overall Survival (OS) was 74% versus 31% ( p = .0011). Transplant related mortality (TRM) was 16% versus 33% ( p = .025), and relapse incidence (RI) was 16% versus 35% ( p = .005). The day‐100 acute Graft‐versus‐host disease (GvHD) incidence grade II–IV and III–IV was 30% versus 28% ( p = NS) and 17% versus 17% ( p = NS). The 3‐year chronic GvHD incidence was 22% versus 33% ( p = NS). Conclusion: Despite all the limits of this retrospective study we were able to show how the combination of BM and ATG is able to prevent GvHDs and guarantee a high OS. Future studies addressing the issue of a post‐transplant cellular therapy approach may potentially reduce relapses when GvHD is absent.